Increased Risk of Pancreatitis after Endoscopic Retrograde Cholangiopancreatography Following a Positive Intraoperative Cholangiogram: A Single-Center Experience - Lalitha M. Sitaraman; Rita M. Knotts; Judith Kim; Srihari Mahadev; David S. Lee (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims To determine if patients with a positive intraoperative cholangiogram (IOC) who undergo a subsequent endoscopic retrograde cholangiopancreatography (ERCP) have an increased risk of post-ERCP pancreatitis (PEP) compared to those who undergo ERCP directly for suspected common bile duct stones. Methods A retrospective case-control study was performed from 2010 to 2016. Cases included inpatients with a positive IOC at cholecystectomy who underwent subsequent ERCP. The control group included age-sex matched cohorts who underwent ERCP for choledocholithiasis. Multivariate logistic regression was used to assess the association between PEP and positive IOC, adjusting for matching variables and additional potential confounders. Results Of the 116 patients that met the inclusion criteria, there were 91 women (78%) in each group. Nine patients (7.8%) developed PEP in the IOC group, compared to 3 patients in the control group (2.6%). The use of pancreatic duct stents and rectal indomethacin was similar in both groups. After adjusting for age, sex, total bilirubin levels, and any stent placement, patients with a positive IOC had a significantly increased risk of PEP (odds ratio, 4.79; 95% confidence interval, 1.05-21.89; p<0.05). Conclusions In this single-center case-control study, there was a five-fold increased risk of PEP following a positive IOC compared to an age-sex matched cohort.